CUSTOMER KNOWLEDGE MANAGEMENT (CKM) USING ORGANIZATIONALLEARNING PROCESSES - Mikuła, Bogusz (Management and Administration Journal, 2024)
The paper addresses the role and essence of customer knowledge management (CKM). The relationship between knowledge management and CKM is described. The main goal is to present the use of organizational learning processes in CKM. Organizational learning processes were characterized based on the author's concept of sub-processes of traditional, empirical and cybernetic organizational learning, the cycles of these processes, changing types of knowledge, main knowledge processes and their categories in CKM. Examples of instruments for implementing organizational learning in CKM are alsoprovided. The publication/article present the result of the Project no 052/ZZZ/2023/POT financed from the subsidy granted to the Krakow University of Economics.